Prudential liquidity regulation in banking: A literature review - Adi Mordel (Bank of Canada, 2018)
Prudential liquidity requirements are a relatively recent regulatory tool on the international front, introduced as part of the Basel III accord in the form of a liquidity coverage ratio (LCR) and a net stable funding ratio (NSFR). I first discuss the rationale for regulating bank liquidity by highlighting the market failures that it addresses while reviewing key theoretical contributions to the literature on the motivation for prudential liquidity regulation. I then introduce some of the empirical literature on the firm-specific and systemwide effects of that regulation. These findings suggest that while banks respond to binding requirements by increasing long-term funding and reducing maturity mismatch, there is also evidence that risk in the financial system has gone up. In an environment where both bank liquidity and capital are regulated, it is natural to consider the interactions between them. The main conclusions from this growing literature indicate that while liquidity requirements tend to make capital constraints less binding, capital requirements appear to be more costly to comply with, and that both regulations have a non-trivial effect on financial stability. I conclude with a discussion of potential avenues to explore as the Basel III liquidity standards are being implemented in Canada.
Keywords: G; G2; G21; G28; 330; Financial institutions; Financial system regulation and policies